1978
DOI: 10.1051/jphyslet:019780039013021300
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for quasi-static scission configurations obtained from long range particle accompanied fission distributions

Abstract: New experimental results on light-particle-accompanied neutron-induced fission of 236U are presented. The widths of the α-particle angular distributions are the same for 236U (nth) and 252Cf(s.f). This angular width appears to be a decreasing function of the total fission fragment kinetic energy. These results suggest that the characteristics of this mode of fission are not inconsistent with a semi-equilibrium model for scission

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Sinha and Mehta [11] have calculated the angular distribution of the long range α particle in the fission of 252 Cf. They could reproduce the experimental results of Guet et al [12] by considering the distance between two main fission fragments D to be less than 20.5 fm as an initial condition in their calculation. In a later work [13], with an improved model, they performed calculations to derive the information on the scission point configuration of spontaneous fission of 252 Cf .…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Sinha and Mehta [11] have calculated the angular distribution of the long range α particle in the fission of 252 Cf. They could reproduce the experimental results of Guet et al [12] by considering the distance between two main fission fragments D to be less than 20.5 fm as an initial condition in their calculation. In a later work [13], with an improved model, they performed calculations to derive the information on the scission point configuration of spontaneous fission of 252 Cf .…”
Section: Introductionmentioning
confidence: 60%
“…It has been concluded that the Lagrange scenario can describe the α accompanied cold ternary fission process. They have done similar calculations for other light charged particles viz., 10 Be and 12 C in the fission of 252 Cf [17]. They reported that the energy and angular distributions strongly depend on the mass asymmetry and the initial position of the third fragment with respect to the two main fission fragments.…”
Section: Introductionmentioning
confidence: 99%
“…1 D6partement de Recherche Fondamentale, CEN-Grenoble, Cedex 85, F-38000 Grenoble, France 2 Institut Laue-Langevin, 156X, F-38042 Grenoble-Cedex, France 3 Division Physique CCR, EURATOM, 1-21020 Ispra, Italie Present address: Gesellschaft fiir Schwerionenforschung, Postfach 110541, D-6100 Darmstadt, Federal Republic of Germany A systematic study [3][4][5] of light-charged-particleaccompanied fission has been undertaken using the very intense neutron beams available at the Grenoble high flux reactor. The present work is devoted to the low energy part of the e-particles energy spectrum for which the experimental results are very scarce (in most experiments, the light-charged-particle detector is shielded against fission fragments) and contradictory.…”
Section: Introductionmentioning
confidence: 99%